Comparing the Trend of Physical Activity and Caloric Intake between Lipid-Lowering Drug Users and Nonusers among Adults with Dyslipidemia: Korean National Health and Nutrition Examination Surveys (2010–2013) - Oh, Jin-Young (Korean J Fam Med, 2016)
BACKGROUND: The purpose of this study was to compare the physical activity and caloric intake trends of lipid-lowering drug users with those of non-users among Korean adults with dyslipidemia. METHODS: This study was a repeated cross-sectional study with a nationally representative sample of 2,635 Korean adults with dyslipidemia based on the 2010–2013 Korea National Health and Nutrition Examination Survey. Physical activity was assessed using the International Physical Activity Questionnaire, and caloric intake was estimated through 24-hour dietary recall. All statistical analyses were conducted using IBM SPSS ver. 21.0 (IBM Co., Armonk, NY, USA). The changes in physical activity and caloric intake were investigated for lipid-lowering drug users and non-users using generalized linear models. RESULTS: The proportion of lipid-lowering drug users in the 2010–2013 survey population increased from 3.5% to 5.0% (P<0.001). Among adults of dyslipidemia, total of 1,562 participants (56.6%) reported taking lipid-lowering drugs, and 1,073 (43.4%) reported not taking lipid-lowering drugs. Drug users were more likely to be older and less educated and to have a diagnosis of diabetes, higher body mass index, and lower low density lipoprotein cholesterol level. Physical activity trends were tested separately for the lipid-lowering drug users and non-users, and a significant decrease was found among the drug users during the study period. Physical activity among the drug users in 2013 was 38% lower (1,357.3±382.7 metabolic equivalent [MET]; P for trend=0.002) than in 2010 (2,201.4±442.6 MET). In contrast, there was no statistically significant difference between drug users and non-users in the trend of caloric intake during the same period. CONCLUSION: Physical activity significantly decreased among lipid-lowering drug users between 2010 and 2013, which was not observed among non-users. The importance of physical activity may need to be re-emphasized for lipid-lowering drug users.